Challenges and Roles of English Public Speaking Courses for Students at the University - Karnedi; Lelly Zuyana Asril; Arif Alexander Bastian (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2026)
This research examined students’ levels of difficulty and their understanding progress in English Public Speaking, key areas of focus include grammar, fluency, vocabulary, comprehension, and accent. Data were taken from 45 students of the English Literature Study Program, Persada Bunda Indonesia University, Pekanbaru, Riau. The mixed research used a questionnaire as an instrument of data collection. The qualitative data in this study complemented the quantitative data, providing a deeper understanding of how and why the Public Speaking course affects students' speaking abilities, particularly in terms of their experiences, attitudes, and perceptions. Overall, the findings indicated that prior to taking the Public Speaking course, students experienced a high level of difficulty in all aspects of English public speaking. The overall mean score of 3.55, categorized as Strongly Difficult, shows that grammar, fluency, vocabulary, comprehension, and accent posed substantial challenges. These results highlight the need for structured public speaking instruction to support students’ English-speaking development. After completing the Public Speaking course, students demonstrated a very high level of understanding across all English public speaking indicators. The overall mean score of 3.63, categorized as Very High, indicates substantial improvement in grammar, fluency, vocabulary, comprehension, and accent. These findings suggest that the Public Speaking course was effective in enhancing students’ English-speaking competence and overall communicative performance.